PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA KARYAWAN DENGAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING (SURVEY PADA KARYAWAN PT. MARINAL INDOPRIMA SUMENEP) - Moh Herman Djaja; Zainurrafiqi Zainurrafiqi (Assyarikah: Journal of Islamic Economic Business, 2021)
In the current era of industry 4.0, the competition for various businesses is increasingly dynamic, for that companies are required to always improve their management so that they can survive and run, so they do not lose in the competition. In order for the company's goals to be achieved, it is necessary to improve the quality of the employee's performance itself, one of the factors that affect employee performance is the leader. A leader who is able to control organizational processes by providing motivation that is able to influence employee performance to achieve organizational goals. The purpose of this study is to determine how much influence transformational leadership has on employee performance through work motivation. This study uses a quantitative method with a descriptive approach. The sample used was 50 respondents, with saturated sampling technique. The type of data used in the form of primary data in the form of questionnaires and secondary data in the form of documents. Analysis of the data used is a path analysis model with SPSS version 21. The results of this study indicate that Transformational Leadership has a positive and significant effect on employee performance. Motivation has a positive and significant effect on employee performance. Transformational Leadership has a positive and significant effect on Motivation, and Transformational Leadership has a positive and significant effect on Employee Performance with Motivation as an intervening variable.Â